Cluster Change Analysis to Assess the Effectiveness of Speaking Skill Techniques using Machine Learning - Wulandari, Nunik Herani; Purwayoga, Vega (Universitas Sanata Dharma, 2025)
This study aims to compare effective teaching methods for speaking using machine learning. The classes used in this study consisted of three classes: conventional, vlog project, and picture series. The data used were students' pre-test and post-test scores. The machine learning algorithm used is K-Means. K-Means clusters the pre-test and post-test data. The results of K-Means clustering on the pre-test and post-test identified the differences in student groups between the pre-test and post-test. Students who experienced the most cluster movement were those in the vlog project class, the conventional class, and the picture series class.